2014
DOI: 10.1556/achrom.26.2014.3.9
|View full text |Cite
|
Sign up to set email alerts
|

Identification and simultaneous determination of glycyrrhizin, formononetin, glycyrrhetinic acid, liquiritin, isoliquiritigenin, and licochalcone A in licorice by LC-MS/MS

Abstract: Summary.A new liquid chromatography-tandem mass spectrometry (LC-MS/MS) method was developed and validated for simultaneous determination of glycyrrhizin, formononetin, glycyrrhetinic acid, liquiritin, isoliquiritigenin, and licochalcone A in licorice. An Eclipse Plus C 18 column (I.D. 4.6 × 100 mm, 3.5 μm particle size; Agilent) was used in the analysis. Electrospray ionization (ESI)-tandem interface in the negative mode was performed, and multiple reaction monitoring (MRM) was employed with the precursor mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 20 publications
1
12
0
2
Order By: Relevance
“…15,16 Quality control of dietary supplements also requires quantitative measurement of chemical constituents in the starting material and in the finished product. In the case of licorice, a variety of analytical methods such as capillary-zone electrophoresis, 17 HPLC-UV, 1822 nuclear magnetic resonance (NMR), 7 HPLC-mass spectrometry, 10 and HPLC-tandem mass spectrometry (MS/MS) 2324 have been used to measure chemical constituents in crude extracts, but rarely in the complex matrices of commercial botanical dietary supplements.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 Quality control of dietary supplements also requires quantitative measurement of chemical constituents in the starting material and in the finished product. In the case of licorice, a variety of analytical methods such as capillary-zone electrophoresis, 17 HPLC-UV, 1822 nuclear magnetic resonance (NMR), 7 HPLC-mass spectrometry, 10 and HPLC-tandem mass spectrometry (MS/MS) 2324 have been used to measure chemical constituents in crude extracts, but rarely in the complex matrices of commercial botanical dietary supplements.…”
Section: Introductionmentioning
confidence: 99%
“…Compounds such as glabridin, hispaglabridin (A and B), 4′-O-methylglabridin, isoprenylchalcone, liquiritigenin, isoliquiritigenin, and formononetin are among the most abundant bioactive phenolic compounds that have been identified so far, with several bioactivity properties. (33)(34)(35)(36)(37) The chemical structure of the main ingredients of liquorice, including glycyrrhizin and glabridin, are shown in Fig. 1.…”
Section: Chemical Compositionmentioning
confidence: 99%
“…Glycyrrhizae Radix (licorice root) has been used as a herbal medicine because of a variety of pharmacological activities, including anti-oxidative, anti-cancer, and anti-diabetic activities as well as memory enhancing and inflammation reducing effects [1]. In addition, it has been used as a flavoring agent in food products [2] and also as an adjuvant to increase the therapeutic efficacy of other drugs. For example, Glycyrrhizae Radix lowers the risk of aphthous ulcers caused by aspirin intake and the side effect of spironolactone.…”
Section: Introductionmentioning
confidence: 99%
“…Glycyrrhizae Radix contains many bioactive saponins and flavonoids along with glycyrrhizin, a major and marker component of Glycyrrhizae Radix [2,4,5,6]. It has recently been reported that glycyrrhizin exerts strong neuroprotective effects on a mouse model of experimental autoimmune encephalomyelitis [1,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation